The Peruvian Government’s Strategy Against Wildlife Trafficking: From Intelligence Operations to Strict Law Enforcement - Abdul Khakim Mahfud ZUBAIDI (Loka: Journal Of Environmental Sciences, 2023)
Purpose:This paper aims to contribute to the literature on wildlife conservation by analyzing the enforcement of organized crime laws as a strategy to combat illegal wildlife trafficking in Peru and protect biodiversity.Methodology:This study employs qualitative descriptive analysis to explore the dynamics of illegal wildlife trafficking in Peru and assess the application of organized crime laws as a mitigation strategy. The research uses secondary data from NGO and INGO reports, academic articles, and government publications from 2018 to 2023.Findings:This study finds that illegal wildlife trade in Peru, driven by market demand and local economic dependency, involves organized criminal networks that threaten biodiversity, necessitating the application of organized crime laws and international collaboration to address the issue.Implication:These findings contribute to the implications is that to tackle illegal wildlife trade in Peru, strengthening law enforcement against organized crime, developing more effective policies to reduce market demand, and enhancing international cooperation are necessary to protect biodiversity and prevent illegal exploitation of wildlife.